Ectopic Expression of the Chinese Cabbage Malate Dehydrogenase Gene Promotes Growth and Aluminum Resistance in Arabidopsis - Li, Qing-Fei; Zhao, Jing; Zhang, Jing; Dai, Zi-Hui; Zhang, Lu-Gang (Frontiers in Plant Science, 2016)
Malate dehydrogenases (MDHs) are key metabolic enzymes that play important roles in plant growth and development. In the present study, we isolated the full-length and coding sequences of BraMDH from Chinese cabbage (Brassica campestris L. ssp. pekinensis (Lour) Olsson). We conducted bioinformatics analysis and a subcellular localization assay, which revealed that the BraMDH gene sequence contained no introns and that BraMDH is localized to the chloroplast. In addition, the expression pattern of BraMDH in Chinese cabbage was investigated, which revealed that BraMDH was heavily expressed in inflorescence apical meristems, as well as the effect of BraMDH overexpression in two homozygous transgenic Arabidopsis lines, which resulted in early bolting and taller inflorescence stems. Furthermore, the fresh and dry weights of aerial tissue from the transgenic Arabidopsis plants were significantly higher than those from the corresponding wild-type plants, as were plant height, the number of rosette leaves, and the number of siliques produced, and the transgenic plants also exhibited stronger aluminum resistance when treated with AlCl3. Therefore, our results suggest that BraMDH has a dramatic effect on plant growth and that the gene is involved in both plant growth and aluminum resistance.